Noise exposure and hearing loss in a steel industry / Muhammad Ismail Harun - Harun, Muhammad Ismail (2012)
Noise induced hearing loss (NIHL) is a sensori-neural hearing deficit that begin at the higher frequencies (3000 to 6000 Hz) and develops gradually as a result of chronic exposure to the excessive sound level. It is mostly found in the developing and industrial countries workers. The objective of this study was to determine the relationship of noise exposure level between exposed and non-exposed group with hearing loss among workers at steel making industry. A cross sectional study was conducted involving 64 respondents from steel industry workers which located at Banting, Selangor. The study was done during the period of March to May 2012. The method of this study included a questionnaire, area noise level monitoring, personal noise monitoring and also audiometric test. The respondents were divided into two groups which is exposed and non-exposed group where each of group consists of 32 respondents. The results of this study were as follows: The noise intensity in the steel making plant range from 62.2 dB(A) to 112.3 dB(A) and in administrative office range from 46.8 dB(A) to 83.3 dB(A) and a number of 24 respondents (75%) of the exposed group got NIHL, compared to 2 respondents (6.3%) of non-exposed group. There was a significant difference in the incidence of NIHL between exposed and non-exposed group. The conclusion is the workers that exposed to high level of noise will develop hearing loss. Immediate corrective action must be taken to prevent this incidence occurs.